The Effect of STEM-Fishbone diagram Learning on Critical Thinking Ability and Self-Efficacy: A Study on High School Students - Puspita, Laila; Hidayah, Nur; Puspitasari, Neneng; Komarudin, Komarudin (Phenomenon : Jurnal Pendidikan MIPA, 2022)
The purpose of this study was to determine the effect of STEM-fishbone diagram learning on critical thinking skills and self-efficacy of high school (SMA) students. This type of research is Quasi-Experimental Design. The population in this study were all students of class XI SMA Al-Kautsar Bandar Lampung. The sampling technique used cluster random sampling, obtained class XI MIPA 5 (experimental class) and class XI MIPA 7 (control class). The collection technique used is in the form of tests and questionnaires. The research instrument used was a test of the ability to think critically and self-efficacy. The technique uses the MANOVA test. The results of the study stated that there was an influence of STEM-fishbone diagram learning on the critical thinking skills and self-efficacy of high school students in Bandar Lampung, besides that it was also known that there was an influence of STEM-fishbone diagram learning on the critical thinking skills of high school students in Bandar Lampung and there was an influence on learning STEM-fishbone diagram on self-efficacy of high school students in Bandar Lampung.